The Needs of Information Services on Reproductive Health, STIs and HIV in Middle Adolescence (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Reproductive health information including STIs and HIV/AIDS has been provided in community health center. In fact, the level of adolescent knowledge in terms of sexual health and its risks is still low. This study aims to identify adolescent needs of information services on sexual and reproductive health including STIs and HIV/AIDS. All adolescent aged 15 to 19 years in Ngesrep village were recruited as a sample. There were 237 adolescents participated in this cross sectional study. The findings showed that half of them have low level of knowledge, nearly half have permissive sexual attitudes, 15% have engaged in sexual intercourse. Adolescents need comprehensive information including pregnancy, sexual diseases and HIV/AIDS which provided by health workers at school health programs.